Design of a sinc-sampled fiber Bragg grating fabricated in high birefringence fiber - 柏青 冯德军 季伟 (Optoelectronics letters, 2011)
In this paper we design a new kind of sinc-sampled fiber Bragg grating which is fabricated in high birefringence fiber （HBF）. The sampled grating has two sets of reflection spectra along two perpendicular polarization directions. The grating＇s channel number can be doubled approximately by designing the refractive index difference between the fast and slow axes of the fiber, which enhances the utilization ratio and reduces the claim for photosensitivity of the fiber. The group delay characteristics are theoretically studied and side-lobes are depressed by apodization as well to get the optimized spectra. The results show that the comb-like spectra of the grating have promising applications in both multi-wavelength polarized fiber lasers and fiber sensing networks.